Integrated Characterization of Phoenix dactylifera L. Fruits and Their Fermented Products: Volatilome Evolution and Quality Parameters - Eloisa Bagnulo; Gabriele Trevisan; Giulia Strocchi; Andrea Caratti; Giulia Tapparo; Giorgio Felizzato; Chiara Cordero; Erica Liberto (Molecules)
Dates (Phoenix dactylifera L.) are nutrient-rich fruits with health-promoting properties and broad applications in the food and beverage industries. This study analyzes the chemical properties and volatile profile of fermented date products—juice, alcoholic derivative, and vinegar—to develop a high-quality vinegar with distinct sensory traits. Using HS-SPME-GC-MS, about 50 volatile compounds were identified across six major chemical classes. Juice processing significantly increased volatile release, especially fusel alcohols and furanic aldehydes, due to thermal and mechanical disruption. Fermentation further modified the volatilome, with increased esters and acids in alcoholic and vinegar products. Vinegar was characterized by high levels of acetic acid, fatty acids, phenols, and acetoin (855 mg/L), indicating active microbial metabolism. Ethanol and acidity levels met international standards. Total phenolic content rose from juice (138 mg/L) to vinegar (181 mg/L), reflecting microbial enzymatic activity and acid-driven extraction. These results highlight the metabolic complexity, sensory richness, and functional potential of date-derived fermented products while promoting sustainable use of underutilized fruit resources.